Numerical simulation of an explosion in a small-scale replica of a Fast Breeder Reactor - Robbe, Marie-France; Lepareux, Michel; Treille, Eloi; Cariou, Yves (Computer Assisted Methods in Engineering and Science, 2022)
A Core Disruptive Accident in a Liquid Metal Fast Breeder Reactor (LMFBR) results from the interaction between molten fuel and liquid sodium, which creates a high-pressure bubble of gas in the core. Theviolent expansion of this bubble loads and deforms the vessel and the internal structures. The MARS experimental test simulates a hypothetical Core Disruptive Accident in a small-scale mock-up containing all the significant internal components of a LMFBR. This paper presents a numerical simulation of thetest with the EUROPLEXUS code.